2017
DOI: 10.1093/rb/rbx024
|View full text |Cite
|
Sign up to set email alerts
|

The material and biological characteristics of osteoinductive calcium phosphate ceramics

Abstract: The discovery of osteoinductivity of calcium phosphate (Ca-P) ceramics has set an enduring paradigm of conferring biological regenerative activity to materials with carefully designed structural characteristics. The unique phase composition and porous structural features of osteoinductive Ca-P ceramics allow it to interact with signaling molecules and extracellular matrices in the host system, creating a local environment conducive to new bone formation. Mounting evidence now indicate that the osteoinductive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
183
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 193 publications
2
183
1
2
Order By: Relevance
“…At day 7, all the aforementioned growth factors in bioceramic groups reduced in comparison to the control. It is worth noting that protein secretion profiles of growth factors were not in accordance with the gene expression results, this may be ascribed to the strong adsorption of Ca‐P ceramics for growth factors as previously reported (Chen, Wang, et al, ; Tang, Li, Tan, Fan, & Zhang, ; Zhu et al, ).…”
Section: Resultsmentioning
confidence: 56%
“…At day 7, all the aforementioned growth factors in bioceramic groups reduced in comparison to the control. It is worth noting that protein secretion profiles of growth factors were not in accordance with the gene expression results, this may be ascribed to the strong adsorption of Ca‐P ceramics for growth factors as previously reported (Chen, Wang, et al, ; Tang, Li, Tan, Fan, & Zhang, ; Zhu et al, ).…”
Section: Resultsmentioning
confidence: 56%
“…Biomaterials are widely used to develop active medical devices capable of promoting tissue regeneration and functional restoration . During these processes, the extracellular matrix (ECM) with its complex and dynamic microenvironment plays a pivotal role in regulating cell adhesion, growth and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials are widely used to develop active medical devices capable of promoting tissue regeneration and functional restoration. 1,2 During these processes, the extracellular matrix (ECM) with its complex and dynamic microenvironment plays a pivotal role in regulating cell adhesion, growth and proliferation. 3,4 Thus, the direct combination of scaffolds functionalized with simplified ECM proteins is widely studied as a promising approach for a broad range of biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…β-TCP with a lower Ca/P ratio of 1.5 possesses better degradability than HA and has been extensively studied for bone regeneration. Moreover, it has been proven that the potential of osteoinductivity is BCP > β-TCP > HA (Samavedi, Whittington, & Goldstein, 2013), which is affected by material characteristics including ionic environment, phase composition, degradation, and structure (Tang, Li, Tan, Fan, & Zhang, 2018). In addition, improvement in maturity of new bone formed by β-TCP is needed as our previous study demonstrated (Li, Liu, et al, 2017).…”
Section: Discussionmentioning
confidence: 90%